Local Government Autonomy and The Grassroots Participation in Governance: Challenges and Prospects - Oghenenyerhovwo Elvis Adogbeji; Mmaduabuchi Onwunyi Ugochukwu (CV. Proaksara Global Transeduka, 2025)
The main aim of this paper is to examine the imperativeness of the recent Supreme Court judgment interpreting the autonomy of local government in Nigeria as enshrined in the 1999 constitution of the Federal Republic of Nigeria and how this could empower more democratic, accountable, and participatory form of governance that aligns with citizens' needs at the community level. The study adopted the secondary source of data gathering to analyze the subject matter under review. This study adopted the qualitative method as data was sourced from secondary sources while the Democratic-Participatory theory formed the analytical framework. The study conclude that local government autonomy is pivotal for fostering grassroots participation and enhancing governance at the community level in Nigeria but the journey toward achieving true autonomy for local governments has been fraught with challenges, yet it holds significant prospects for democratic deepening and sustainable development with the new supreme court judgement. The study recommend among others that the July 11th, 2024 Supreme Court judgment that grant financial and administrative autonomy to local governments should be followed to the latter ensuring direct allocation of funds to the local governments without state interference.